Soluble factors and suppressive monocytes can predict early development of sepsis in acute‐on‐chronic liver failure. Issue 8 (2nd May 2022) - Yadav, Pushpa; Trehanpati, Nirupama; Maiwall, Rakhi; Sehgal, Rashi; Singh, Ravinder; Islam, Mojahidul; Jagdish, Rakesh Kumar; Vijayaraghavan, Rajan; Maheshwari, Deepanshu; Bhat, Sadam; Kale, Pratibha; Kumar, Anupam; et al.
Abstract: Patients with acute‐on‐chronic liver failure (ACLF) have a high probability of developing systemic inflammation and sepsis due to immune dysregulation. Fifty‐nine patients with ACLF (12 without and 19 with systemic inflammation, and 28 with sepsis) were serially monitored for clinical and immunological changes at baseline, 6 hours, 24 hours, day 3, and day 7 following hospitalization. Ten healthy controls were also included. At all time points, soluble plasma factors and monocyte functions were studied. Patients with ACLF and systemic inflammation showed higher interleukin (IL)–6, vascular endothelial growth factor‐a, monocyte chemoattractant protein 1, and macrophage inflammatory protein 1β than patients with no systemic inflammation. Patients with ACLF with sepsis had raised ( p  < 0.001) levels of IL‐1Ra, IL‐18, and triggering receptor expressed on myeloid cells 1 (TREM1) compared to patients with ACLF‐systemic inflammation. Five of the 19 (26.3%) patients with systemic inflammation developed sepsis within 48–72 hours with a rapid rise in plasma levels of IL‐1Ra (1203–35, 000 pg/ml), IL‐18 (48–114 pg/ml), and TREM1 (1273–4865 pg/ml). Monocytes of patients with ACLF with systemic inflammation and sepsis showed reduced human leukocyte antigen–DR but increased programmed death ligand 1 (PD‐L1) and T‐cell immunoglobulin and mucin domain‐containing protein 3 (TIM3) ( p  < 0.04) expression with increased ETosis by monocytes at baseline and until day 7. Conclusion: High and rising levels of plasma IL‐1Ra, IL‐18, TREM1 soluble factors, and increased suppressive monocytes (PDL1 +ve, TIM3 +ve ) at baseline can stratify patients with ACLF at high risk of developing sepsis within 48–72 hours of hospitalization. Abstract : ACLF is a liver disease with high short‐term mortality. It is associated with immune dysfunction and the development of sepsis. There are few markers of early detection of sepsis. We propose that elevated levels of some biomarkers (IL‐1Ra, IL‐18, and TREM‐1) can be used to identify patients with ACLF who are at risk of developing sepsis. Additionally, the immune cells and monocytes from these patients have suppressive (high suppressive markers, PDL1 and TIM3) and are exhausted (low HLA‐DR) increasing susceptibility to infections.image